KOORDINASI APARAT PENGAWASAN INTERN PEMERINTAH (APIP) DAN PENYIDIK DALAM PENANGANAN TINDAK PIDANA KORUPSI DI KABUPATEN BANYUMAS - Nunik Sri Wahyuni (Jurnal Idea Hukum, 2017)
This research aimed to find out the form and coordination effectiveness between the Government Intern Controlling Apparatus with the Investigator  in handling the criminal act of corruption in the Regency of Banyumas  This research used the sociology juridical approach. Data in this research was obtained by interview with the Public Attorney Investigator of Banyumas. The Tipikor Unit Investigator  Reskrim Polres Banyumas and Inspektorat Banyumas  and  collecting  many of the  certainty ordinance regulation, documentation, literature and accessing  internet.   Based on the  result of research and  discussion  could be  taken  the  conclusion of. Coordination between APIP and Investigator  did not have  the  clearness  in  technique  and criteria act of State Civil Apparatus which one was  categorized   in the scope of  criminal act that became  the  authority of Investigator  or in the scope of  administration  that  became the authority of APIP with the Investigator  in handling the  criminal act of corruption   was not  being effective  because of ego sectoral between APIP and Investigator and the necessity of disposition of regebts so that APIP can not work objectively and take a very long time. Keywords: APIP, Coordination, Investigator